PENGARUH AKTIVITAS ZIARAH TERHADAP RUANG PUBLIK ALUN-ALUN STUDI KASUS : KAWASAN PEMAKAMAN SUNAN BONANG - Lidya Mahardhika Allan; Mila Karmilah (Universitas Islam Sultan Agung Semarang, 2017)
Tuban town square are included in one of the utilization of active open space in the Tuban area. The town square is located in the city center and near of the many tourism objects in Tuban. One of them such us Sunan Bonang Funeral. The goals of this study are to verivy the effect of pilgrimages acivity to the public open space of Tuban town square. The Targets to be achieved, such us :1) Identification the effect based on characteristics Type of Activities in the Sunan Bonang Funeral Pilgrimage Area, 2) Identification the effect based on characteristics Type of activity Around the Public Open Space, 3) Analysing the factors that affect the pilgrimage activity to the public open space. 4) Verivy the affectthe pilgrimage activity to the public open space. Hypothesisin this studyare have or have no effect of pilgrimage activitytothe public open space of Tuban town square.So it can be seen the factors that effect of the pilgrimage activity to the public open space, and also presence the effect caused by pilgrimage activity to the public open space of Tuban town square.Keywords: Activity, Pilgrimage area, Public Open Space